Defence takes the floor! - Jurisdiction, concept of economic unity and protection of the weaker party - Manenti, Andrea (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The article tackles the evolution in the case law of the Court of Justice of the European Union of the concept of economic unity starting from the recent Heineken judgment. The analysis is focused particularly on the problems that the current general approach creates in relation to the burden of proof in antitrust proceedings and the protection of the defense’s rights. In the end, considering the Court of Justice established case law, the article examines – with some critical notes – how the concept is used by national courts during the evaluation of their own jurisdiction.